MULTIFUNCTIONAL NANOSYSTEMS BASED ON TWO FLUORESCENT DYES, DOXORUBICIN AND CURCUMIN - M. I. KANIUK (Biotechnologia Acta, 2022)
The aim of the work was to review the literature data regarding the prospects for the creation and use of multifunctional fluorescent two-dye nanosystems, which enable investigating the distribution of fluorescent components with significant acceleration of the study and introduction of nanomedicines into practice. Special attention is paid to the use of two substances with hydrophobic and hydrophilic properties in one nanoparticle (NP), capable of penetrating a living cell. The method of fluorescence confocal microscopy enables observation of the nanoscale dynamics of distribution and stability of drugs over time. The concomitant use of doxorubicin (DOX) and curcumin (CUR) in single nanoparticle causes synergism in the action of medical drugs, and their own fluorescence makes it possible to use them as multifunctional fluorescent nanosystems.